Suitability of Enteric Coated Iron and Folic Acid Tablets in WIFS Program in India - Kapil, Radhika (Indian Journal of Community Health, 2018)
Weekly iron folic acid supplementation (WIFS) programme is being implemented by Government of India for Prevention and control of anaemia amongst Adolescents since 2013. Under this program, enteric coated Iron and Folic Acid (IFA) tablet consisting of 100 mg of elemental iron with 500 mcg of folic acid, is given every week to all adolescent girls. Evidence suggests that there is a low absorption of iron from the enteric coated (EC) IFA tablets. The poor clinical response of EC IFA compared to the conventional sugar coated has also been reported The, present review describes the WIFS programme, cost, composition, evidence on absorption, clinical response on Hb from EC IFA tablets. There is an urgent need to take cognizance of available scientific evidence in to consideration and discontinue the EC tablets from WIFS programme.